The difference of nasal mucosal cytology features in gas station workers compared to non-gas station workers - Rianto, Bambang Udji Djoko; Kurniawan, Linggawati; Sudarman, Kartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2019)
The pollutants contained in an outdoor air environment for example gasoline vapors can cause epithelial inflammation, metaplasia, and dysplasia. This study aimed to determine the difference in cytological nasal mucosa between gas station workers and non-gas station workers. This research used a cross-sectional design. There were 80 samples with inclusion criteria: aged 20-50 years, worked more than 3 months, consisting of 40 gas station workers (exposed group) and 40 non-gas station workers (unexposed group) who did not use nasal drops in the last ten days. The exclusion criteria of both groups were: 1) patients with acute rhinitis, 2) had nasal trauma, 3) had nasal surgery, 4) consume alcohol, 5) history of allergic rhinitis, and 6) refused to participate in the study. All samples performed brushing at 1/3 anterior nose inferior turbinate and cytology examination. The statistical analyses used X2 tests. From the exposed group we found 18 (45%) with inflammation, 17 samples (42.5%) with metaplasia, and 9 samples (22.5%) with dysplasia, while in the unexposed group there were 10 (20.5%) with inflammation, 4 (10.0%) with metaplasia and 2 (5.0%) dysplasia. There were statistically significant differences in nasal mucosal cytology, particularly metaplasia (p: 0.001; RP: 6.65; 95% CI: 1.78-27.01) and dysplasia (p: 0.023; RP: 5.52; 95% CI: 1.22-32.10) between both group samples. It can be concluded that there are statistically significant differences involving metaplasia and dysplasia in nasal mucosa cytology features of gas station workers compared to non-gas station workers.